WEWENANG KELEMBAGAAN PENGELOLAAN LINGKUNGAN HIDUP DI ERA OTONOMI DAERAH - Muhammad Akib (Jurnal Media Hukum, 2012)
The aims of this study are to assess the regulation regarding institutional authority of local environmental management agencies and discover the strong regulation model and reflect the principles of local autonomy and ecological sustainability. The research used doctrinal legal research method by using primary legal materials and secondary legal materials and analyzed in a prescriptive-analysis. The research discover that the regulations regarding local environment management agencies are weak, due to uncertainty and lack of local authority, different nomenclature, and the absence of clear regulation on inter-institutional relations procedure. The future regulation model, the local environmental management agencies should have a broad authority, covering planning, implementation, monitoring and enforcement aspects. Duties and functions must integrate coordination and operational functions, and there is a clear relationship system encompassing both inter-institutional and inter-regional center.Key word: authority, institutional, local autonomy